The Impact of Credit Risk and Operational Efficiency on Profitability and Its Implications on the Capitalization of Bank Perekonomian Rakyat Wibawa Mukti Jabar During the 2019-2023 Period - Devi Puspitasari; Cecep Taufiqurrochman (Green Publisher Indonesia, 2026)
This research is motivated by the importance of the financial performance of the People's Economic Bank (BPR) in maintaining the stability of the national financial services sector in accordance with the mandate of Law Number 21 of 2011 concerning the Financial Services Authority. BPR has a strategic role in encouraging local economic growth, especially through the disbursement of credit to MSMEs and the community. However, BPR's financial performance nationally shows a downward trend in 2023, reflected in declining profitability (ROA), a worsening operational efficiency ratio (BOPO), and increasing credit risk (NPL). The analysis method used is financial ratio analysis with reference to BPR Wibawa Mukti Jabar's annual financial statements, supported by theories and previous research results. The research method used was quantitative analysis with a multiple regression approach. The results show that credit risk, operational efficiency, and capital have a significant influence both partially and simultaneously on profitability. These findings provide important implications for bank management to increase profitability through controlling non-performing loans, improving operational cost efficiency, and strengthening capital in accordance with regulatory standards.